Iatrogenic air embolism: influence of air bubble size on cerebral infarctions in an experimental in vivo and numerical simulation model - Schaefer, Tabea; Greive, Svenja; Bierwisch, Claas; Mohseni-Mofidi, Shoya; Heiland, Sabine; Kramer, Martin; Möhlenbruch, Markus Alfred; Bendszus, Martin; Vollherbst, Dominik (Journal of neuroInterventional surgery, 2023)
Background Cerebral infarctions resulting from iatrogenic air embolism (AE), mainly caused by small air bubbles, are a well-known and often overlooked event in endovascular interventions. Despite their significance, the underlying pathophysiology remains largely unclear. - Methods In 24 rats, AEs were induced using a microcatheter, positioned in the carotid artery via femoral access. Rats were divided into two study groups, based on the size of the bubbles (85 and 120 µm) and two sub-groups, differing in air volume (0.39 and 0.64 µl). Ultra-high-field magnetic resonance imaging (MRI) was performed 1.5 hours after intervention. MRI findings including the number, single volume and total volume of the infarctions were assessed. A software-based numerical simulation was performed to qualitatively assess the microvascular pathomechanisms. - Results In the study groups 22 of 24 rats (92%) revealed cerebral infarctions. The number of infarctions per rat was higher for the smaller bubbles, for the lower (medians: 5 vs 3; p=0.049) and higher air volume sub-groups (medians: 6 vs 4; p=0.012). Correspondingly, total infarction volume was higher for the smaller bubbles (1.67 vs 0.5 mm³; p=0.042). Simulations confirmed the results of the experiments and suggested that fusion of microbubbles to larger bubbles is the underlying pathomechanism of vascular occlusions. - Conclusion In iatrogenic AE, the size of the bubbles can have a major impact on the number and total volume of cerebral infarctions. These findings can help to better understand the pathophysiology of this frequent, often underestimated adverse event in endovascular interventions.